1974
DOI: 10.1002/pol.1974.180120508
|View full text |Cite
|
Sign up to set email alerts
|

Properties of cellulose acetate in solution. I. Light scattering, osmometry, and viscometry on dilute solutions

Abstract: Light‐scattering, osmotic pressure, and viscometric studies on fractions of cellulose acetate (degree of substitution 2.45) in three solvents are described. The data yield the dependence of the mean‐square radius of gyration 〈s2〉, the second virial coefficient Γ2, and the intrinsic viscosity [η] on molecular weight M and temperature. The results are interpreted to show that excluded volume effects on 〈s2〉 are negligible, even though Γ2 is large and dΓ2/dT is positive. The large experimental value of d In [η]/d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
1

Year Published

1979
1979
2006
2006

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(31 citation statements)
references
References 37 publications
(6 reference statements)
3
27
1
Order By: Relevance
“…22 The chain expansion of CTC with decreasing temperature was reported by several workers. [22][23][24][25][26] The values of k 0 are normal, indicating no aggregation of CTC in THF upon cooling. Figure 2 plots [] vs. M w double-logarithmically of CTC in THF at 0 and À25 C as well as the previous results at 25 C. 9 The molecular weight dependencies of [] become slightly stronger with lowering temperature.…”
Section: Resultsmentioning
confidence: 99%
“…22 The chain expansion of CTC with decreasing temperature was reported by several workers. [22][23][24][25][26] The values of k 0 are normal, indicating no aggregation of CTC in THF upon cooling. Figure 2 plots [] vs. M w double-logarithmically of CTC in THF at 0 and À25 C as well as the previous results at 25 C. 9 The molecular weight dependencies of [] become slightly stronger with lowering temperature.…”
Section: Resultsmentioning
confidence: 99%
“…In a different and somewhat unusual, but not unique, example, it has been reported that Kc/R Vv (ϑ,c) is linear in q 2 , albeit giving a molecular weight that is much larger than the true value of M w for the solute. (139) This was observed with a system that formed a gel at a higher solute concentration, suggesting that the observed scattering behavior reflects the anticipated P Vv (ϑ,c) for a randomly branched polymer. (6) More frequently, with intermolecular association involving flexible chain polymers, Kc/R Vv (ϑ,c) exhibits enhanced scattering at small q.…”
Section: Intermolecular Associationmentioning
confidence: 76%
“…8 The acetyl content of each fraction was determined by the alkaline hydrolysis The characteristics of the samples used in this study are summarized in Table I.…”
Section: Methodsmentioning
confidence: 99%
“…II, No. 8,1979 did not attempt to promote the crystallization of CT A and CDA films by streching or rolling, since our purpose was only to compare the X-ray diffraction pattern of the gel with that of CT A and CDA films. Although the X-ray diffraction patterns of CTA and CDA films did not show high crystallinity, the patterns nevertheless indicate that the cellulose triacetate form I crystallites 9 exist in the films.…”
Section: X-ray Diffraction Ofmentioning
confidence: 99%